Species-specific gene expression manipulation in humanized livers of chimeric mice via siRNA-encapsulated lipid nanoparticle treatment - Kazuto Yamazaki; Kenji Kubara; Go Sugahara; Hiroki Muto; Masae Yamamoto; Yuji Mano; Kaoru Mitsuhashi; Chihiro Yamasaki; Yuji Ishida; Chise Tateno; Yuta Suzuki (Molecular Therapy: Methods & Clinical Development)
Liver-humanized chimeric mice (PXB-mice) are widely utilized for predicting human pharmacokinetics (PK) and as human disease models. However, residual metabolic activity of mouse hepatocytes in chimeric mice can interfere with accurate human PK estimation. Lipid nanoparticle (LNP)-formulated small interfering RNA (siRNA) treatment makes it possible to eliminate the shortcomings of chimeras and create new models. Therefore, we aimed to create a new model in which siRNA for mouse cytochrome P450 oxidoreductase (Por) gene was encapsulated in LNP and administered to PXB-mice. We validated the siRNA-LNP system in PXB-mice, showing that a single intravenous injection of LNP-formulated mouse-specific siRNA against transthyretin (Ttr) knocked down Ttr expression in the liver and decreased plasma mouse TTR levels without affecting hepatic TTR expression and plasma human TTR levels. We produced mouse Por-specific siRNA with high in vitro silencing activity (siPOR(Mm)) and confirmed the efficient knockdown of Por expression in the livers of PXB-mice administered intravenously with LNP-encapsulated siPOR (siPOR(Mm)/LNP). siPOR(Mm)/LNP treatment suppressed 4′-hydroxywarfarin, making the S-warfarin PK profile in PXB-mice more similar to that in humans. Thus, mouse-specific siRNA-LNP is a simple system to control gene expression in the remaining mouse hepatocytes of PXB-mice and create more humanized and invaluable models based on PXB-mice.